Adolescents and parental caregivers as lay health advisers in a community-based risk reduction intervention for youth: baseline data from Teach One, Reach One. Issue 4 (2nd April 2016) - Ritchwood, Tiarney D.; Dave, Gaurav; Carthron, Dana L.; Isler, Malika Roman; Blumenthal, Connie; Wynn, Mysha; Odulana, Adebowale; Lin, Feng-Chang; Akers, Aletha Y.; Corbie-Smith, Giselle
ABSTRACT: The purpose of the current study is to describe the demographic, behavioral, and psychosocial characteristics of adolescent and caregiver lay health advisers (LHAs) participating in an intervention designed to reduce risk behaviors among rural African-American adolescents. Teach One, Reach One integrates constructs from the Theory of Planned Behavior and Social Cognitive Theory. It acknowledges that changing the sexual behaviors of African-American adolescents requires changing one's knowledge, attitudes, normative beliefs about the behavior of peers, and self-efficacy regarding adolescent sexual behavior, parent–teen communication about sex, and healthy dating relations among adolescents. Study participants completed baseline questionnaires assessing demographics and psychosocial determinants (knowledge, attitudes, perceived social norms, and self-efficacy) of sexual behaviors. Sixty-two adolescent and caregiver dyads participated. Caregivers included biological parents, legal guardians, or other parental figures. Strengths and areas in need of improvement were determined using median splits. Few adolescents had initiated sex. Their strengths included high levels of open parent–teen communication; positive attitudes and normative beliefs regarding both sex communication and healthy dating relationships; and high knowledge and self-efficacy for healthy dating behaviors. Areas needing improvement included low knowledge, unfavorable attitudes, poor normative beliefs, and low self-efficacy regarding condom use. Caregiver strengths included positive attitudes, normative beliefs, and self-efficacy for sex communication; positive attitudes and self-efficacy for condom use; and low acceptance of couple violence. Areas needing improvement included low levels of actual communication about sex and low knowledge about effective communication strategies and condom use. The current study highlights the value of assessing baseline characteristics of LHAs prior to intervention implementation, as it enables a better understanding of the key characteristics necessary for planning and implementing interventions, as well as engaging in targeted training activities.